Stress-induced release of Oct-1 from the nuclear envelope is mediated by JNK phosphorylation of lamin B1. - Ivan I Boubriak; Ashraf N Malhas; Marek M Drozdz; Lior Pytowski; David J Vaux (PLoS ONE)
The nuclear lamina can bind and sequester transcription factors (TFs), a function lost if the lamina is abnormal, with missing or mutant lamin proteins. We now show that TF sequestration is not all-or-nothing, but a dynamic physiological response to external signals. We show that the binding of the ubiquitous TF, Oct-1, to lamin B1 was reversed under conditions of cellular stress caused, inter alia, by the chemical methylating agent methylmethanesulfonate (MMS). A search for lamin B1 post-translational modifications that might mediate changes in Oct-1 binding using kinase inhibitors uncovered a role for c-Jun N-terminal kinase (JNK). Phosphoproteomic and site-directed mutagenesis analyses of lamin B1 isolated from control and MMS-treated nuclei identified T575 as a JNK site phosphorylated after stress. A new phospho-T575 specific anti-peptide antibody confirmed increased interphase cellular T575 phosphorylation after cell exposure to certain stress conditions, enabling us to conclude that lamin B1 acts as an interphase kinase target, releasing Oct-1 to execute a protective response to stress.